THE EFFECT OF E-SERVICE QUALITY AND PERCEIVED VALUE ON E-TRUST WITH E-SATISFACTION AS A MEDIATION VARIABLE (STUDY ON CUSTOMERS WHO ONLINE SHOPPING IN THE SHOPEE APP DURING COVID-19 PENDEMIC IN INDONESIA) - Yefrinal Andra; Verinita Arsya; Eri Besra (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
The rapid development of e-commerce in Indonesia makes businesses compete in building their business through e-commerce. In order to be competitive, e-commerce must improve the quality of e-service quality and perceived value so as to gain market share and valuation. This study aims to examine the effect of e-service quality and perceived value on e-trust with e-satisfaction as a mediating variable (Study on customers who shop online on the Shopee application during the Covid-19 pandemic in Indonesia. With data processing the research is carried out through Smart PLS 3.3 The sampling technique used purposive sampling with a sample size of 400 samples. E-service quality affects e-satisfaction. Perceived value has an effect on e-satisfaction. E-satisfaction has no effect on e-trust. E-service quality affects e-trust. Perceived value has an effect on e-trust. E-service quality has no effect on e-trust through e-satisfaction as a mediating variable. Perceived value has no effect on e-trust through e-satisfaction as a mediating variable.